Selecting Media for Knowledge Transfer: Experience from the Field - Abu Hassan, Musa (Universiti Putra Malaysia Press, 1995)
This study examines the ways in which staff of communication units in agricultural development agencies select media to transfer knowledge to their clients. A survey for data collection was conducted and 95 staff of communication units from 11 development agencies were asked to respond to self administered questionnaires. Most of the questions were open-ended and ratings of items for frequency and applicability were on a scale of 1 to 7 . The study revealed that the respondents regarded actual objects or realia best in knowledge transfer activities, followed by media that convey a high degree of fidelity. The respondents also indicated that media for instruction are somewhat different from media for campaigns. The selection elements considered important in the media selection process were audience characteristics, followed by purpose of communication, audience's media preference, and time given to prepare the media.